Exposure to 26.5 GHz, 5G modulated and unmodulated signal, does not affect key cellular endpoints of human neuroblastoma cells - Anna Sannino; Mariateresa Allocca; Maria Rosaria Scarfì; Stefania Romeo; Valentina Peluso; Gaetano Panariello; Fulvio Schettino; Gaetano Chirico; Olga Zeni (Scientific Reports)
Abstract The fifth generation (5G) network is currently being worldwide spread out, raising questions about its potential health impact. The current study aimed to investigate the effects of a 26.5 GHz 5G electromagnetic field on key cellular endpoints of human neuroblastoma cells. A reverberation chamber-based exposure system was designed and realized which allowed the exposure/sham exposure of cell cultures under highly controlled exposure conditions of both electromagnetic and biological parameters. The suitability of the reverberation chambers to host cell cultures was verified by evaluating cell proliferation and cell cycle progression. The effect of 3 h exposure at specific absorption rate of 1.25 W/kg under both continuous wave and 5G modulated signal was evaluated in terms of cell cycle and DNA damage. In the latter case, the exposure was also given in combination with menadione to account for possible cooperative effects. Results showed absence of effects of exposure given alone and in combination with menadione, when both continuous wave and modulated signals were applied at the mentioned exposure level. Further investigations are needed by varying the exposure and biological parameters to strengthen the absence of effects due to 5G signals in the range of millimeter waves.